The Effect of E-LKPD Based on Physics Toolbox Sensor Suite on Simple Harmonic Motion Material on High School Students' Understanding of Physics Concepts - Distrik, I Wayan; Wulandari, Arini; Viyanti, Viyanti (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
This research aims to determine the effect of Digital-Worksheet (E-LKPD) with the Physics Toolbox Sensor Suite on understanding physics concepts of high school students in South Lampung, Lampung. A total of 60 students were involved in this research and were divided into two classes, namely the experimental and control classes. Data were analyzed using n-gain, independent sample t-test, and effect size. The research results showed that the average N-gain in the experimental class was 0.73 in the high category, while it was 0.58 in the medium category in the control class. There was a significant difference in n-gain in understanding concepts (sig.2-tailed < 0.05) between the experimental and control classes. This result is also reinforced by the effect size, which is very high, namely 1.319. This shows that the E-LKPD with the Physics Toolbox Sensor Suite is able to improve understanding of physics concepts, especially regarding Vibration. E-LKPD with the Physics Toolbox Sensor Suite can help students understand concepts, improve work activities, and reduce misconceptions.